Prevalence and risk factors of mastitis in dairy cows in Chattogram, Bangladesh - Kazi Shams Al Arefin; Tanvir Ahmad Nizami (Veterinary Research Notes)
Objective: This study aimed to estimate the prevalence and risk factors of subclinical and clinical mastitis in dairy cows in northwestern Chattogram, Bangladesh, using the California Mastitis Test (CMT). Materials and Methods: We performed CMT by collecting milk samples from each udder quarter to detect subclinical mastitis. Data were collected over 3 months from 102 cows in dairy farms and individual holdings and analyzed using descriptive statistics. Results: The results revealed that 23.53% of cows were affected with mastitis, whereas clinical mastitis was found in 8.82% of cows, and subclinical mastitis was found in 14.71% of cows. The highest prevalence of mastitis (33%) was found in Holstein Friesian and Sahiwal crossbreeds (p = 0.007). Mastitis was more likely to occur in the 4–5 months of the lactation period (50%) and 2–3 years of age groups (56%). In addition, cows with a milk yield between 11–15 l/day had the highest mastitis prevalence (53%). Milking systems also influenced mastitis, with a prevalence of 54% in hand-milking systems and 96% in systems involving multiple milkers. Strong biosecurity significantly reduced mastitis cases, with only 12.5% of mastitis cases on farms maintaining good biosecurity. Intensive farming systems had the highest prevalence (83%), compared to semi-intensive (12.5%) and extensive systems (4%). Floor types such as concrete floors had 96% of mastitis cases, whereas mud floors had only 4% of cases. Conclusion: The occurrence of mastitis increases with high milk yield, advanced age, mid-lactation stage, involvement of multiple milkers, poor health management, and an intensive rearing system. [Vet. Res. Notes 2025; 5(4.000): 33-39]